The Role of Features in Determining the Order of Merge - Seyed Mahdi Sadati Nooshabadi; Mehdi Sabzevari; Narjes Banou Sabouri; MAZDAK ANUSHE (مطالعات زبانی و بلاغی)
Features as the syntactic foundation of the sentence constituents have a special role in the syntactic operations and derivation of the sentence. Merge operation is responsible for the combination of the constituents and derivation of the sentence. In the derivation of the sentence, the constituents are put together based on the hierarchy of the projections but this question is raised that how the computational system of Language determines the order of merge for constituents and prevents the syntactic ill-formed sentences. In this paper based on the proposed “Proper Inclusion Relation” which regulates the order of merge for constituents, the derivation of sentences in the Persian language is studied. Based on this proposed relation, the computational system of Language only uses the constituents to merge and move that their morphosyntactic features are in Proper Inclusion Relation with each other. The results of this paper show that based on the theoretical foundation of this relation and considering the morphosyntactic features of the constituents in the Numeration and workspace of the computational system, the order of merge and the derivation of the sentence in the Persian language can be explained. Moreover, this relation can explain the free order of the adjunct in the Persian language well.